1998
DOI: 10.1007/s002709900207
|View full text |Cite
|
Sign up to set email alerts
|

Salpingitis Isthmica Nodosa: Technical Success and Outcome of Fluoroscopic Transcervical Fallopian Tube Recanalization

Abstract: FTR in SIN is technically successful and, compared with previously reported results in unselected infertility patients, is associated with only a slightly less favorable intrauterine pregnancy rate and a comparable ectopic pregnancy rate. The findings of SIN at FTR should not discourage attempted fluoroscopic transcervical recanalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The authors concluded that FTR in SIN is associated with good results and, compared with previously reported results in unselected infertility patients, is associated with only a slightly less favorable intrauterine pregnancy rate and a comparable ectopic pregnancy rate. 12 Proximal tubal obstruction caused by muscular, tubal or cornual spasms, viscid secretions, mucosal aggregates, amorphous debri or stomal edema can be managed by FTR with a good success rate. The FTR may not bear satisfactory results in cases with tubal obstruction secondary to endometriosis, chronic tubal edema or inflammation (Salpingitis) and cornual polyps.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that FTR in SIN is associated with good results and, compared with previously reported results in unselected infertility patients, is associated with only a slightly less favorable intrauterine pregnancy rate and a comparable ectopic pregnancy rate. 12 Proximal tubal obstruction caused by muscular, tubal or cornual spasms, viscid secretions, mucosal aggregates, amorphous debri or stomal edema can be managed by FTR with a good success rate. The FTR may not bear satisfactory results in cases with tubal obstruction secondary to endometriosis, chronic tubal edema or inflammation (Salpingitis) and cornual polyps.…”
Section: Discussionmentioning
confidence: 99%
“…9 Fallopian tube recanalization in SIN is technically successful and, compared with previously reported results in unselected infertility patients, is associated with only a slightly less favourable intrauterine pregnancy rate and a comparable ectopic pregnancy rate. 10 We believe that this is the ®rst report describing the use of a 5-mm diagnostic hysteroscopic sheath, normal saline as distending medium, and a 0.018-inch Terumo hydrophilic guide wire along with a Labotect¯exible catheter guide cannula with a ball-shaped tip.…”
Section: Introductionmentioning
confidence: 89%
“…An identified tubal disease such as salpingitis isthmica nodosa, or even tubal endometriosis, is not a contraindication [13]. The decision to undertake selective recanalization should ideally be taken following consultation between the radiology and gynecology department.…”
Section: Technique Of Hsgmentioning
confidence: 97%